2018
DOI: 10.3390/catal8090385
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Sustainable Synthesis of Propanols from Renewable Glycerol over MoO3-Al2O3 Supported Palladium Catalysts

Abstract: The catalytic conversion of glycerol to value-added propanols is a promising synthetic route that holds the potential to overcome the glycerol oversupply from the biodiesel industry. In this study, selective hydrogenolysis of 10 wt% aqueous bio-glycerol to 1-propanol and 2-propanol was performed in the vapor phase, fixed-bed reactor by using environmentally friendly bifunctional Pd/MoO3-Al2O3 catalysts prepared by wetness impregnation method. The physicochemical properties of these catalysts were derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Previous work [70] reported conclusive explanation about the H 2 pressure suggesting that higher H 2 pressure promotes excessive hydrogenolysis of glycerol conversion towards lower alcohols like 1-propanol, 2-propanol and ethylene glycol. On the other hand, in an earlier paper [5] it was reported that high concentration of glycerol may decrease glycerol conversion.…”
Section: Glycerol Conversionmentioning
confidence: 94%
“…Previous work [70] reported conclusive explanation about the H 2 pressure suggesting that higher H 2 pressure promotes excessive hydrogenolysis of glycerol conversion towards lower alcohols like 1-propanol, 2-propanol and ethylene glycol. On the other hand, in an earlier paper [5] it was reported that high concentration of glycerol may decrease glycerol conversion.…”
Section: Glycerol Conversionmentioning
confidence: 94%
“…It is again evident that high temperatures produce a significant increase in the rate of the hydrolysis reaction. Figure 8 shows surface plots for this response obtained from Equation (8), which correlates the generation of the diglycerides with the evaluated factors with a R 2 = 95.9%.…”
Section: • Generation Of Diglycerides Formed By Capric and Palmitic Acidmentioning
confidence: 99%
“…There is thus an increasing surplus of glycerol, creating a need to develop alternative ways to use residual glycerol. 2 Due to its high functionalization, glycerol can be transformed into several value-added products ( Table 1), such as lactic acid, [3][4][5] glyceric acid, 6-8 glycolic acid, [9][10][11] oxalic acid, 9,12 dihydroxyacetone, [13][14][15] glyceraldehyde, [16][17][18] 1,2-propanediol, [19][20][21] 1,3-propanediol, 22-24 1-propanol, 25,26 acrylic acid, [27][28][29] acrolein, [30][31][32] syngas, [33][34][35] mono-, di-, tri-glycerides, [36][37][38] triacetin, [39][40][41] glycerol oligomers, 42,43 and polymers. 44 Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry 45,46 as raw material for the production of pharmaceuticals, 47 cosmetics, 48 textiles, 49 leather,…”
Section: Reactionmentioning
confidence: 99%
“…Due to its high functionalization, glycerol can be transformed into several value‐added products (Table ), such as lactic acid, glyceric acid, glycolic acid, oxalic acid, dihydroxyacetone, glyceraldehyde, 1,2‐propanediol, 1,3‐propanediol, 1‐propanol, acrylic acid, acrolein, syngas, mono‐, di‐, tri‐glycerides, triacetin, glycerol oligomers, and polymers . Lactic acid is conventionally used as an acidulant and preservative in the food industry, in the chemical industry as raw material for the production of pharmaceuticals, cosmetics, textiles, leather, and, in a fast‐growing niche market, as monomer for the biodegradable polymer poly‐(lactic acid) or PLA .…”
Section: Introductionmentioning
confidence: 99%